Projects Based Learning To Increase Entrepreneurial Interest For Student Entrepreneurship Program - Permana, Agus Aan Jiwa (Journal of Education Reseach and Evaluation, 2018)
In an effort to encourage the nations economic development through the potential of vocational education in an effort to reduce unemployment and create employment in Indonesia. The government provides opportunities for students to entrepreneurship. With experience about entrepreneurship expected by students after graduating from university students can independently develop business in various sectors. This study aims to help students who have difficulty in pouring their creative ideas into a proposal. This is certainly received serious attention through the process of intense guidance from lecturers especially for students who have never written a paper. In maximizing the potential that exists in a limited time, the development of ideas into proposals can be done by utilizing the time on project management lectures and information systems management with project-based learning methods. The result is that students can learn to write project proposals and produce products that help students in joining entrepreneurship programs.Keywords:one or more word(s) or phrase(s), that itâs important, spesific, or representative for the article.Â